Half-dose fulvestrant plus anastrozole as a first-line treatment for hormone receptor-positive metastatic breast cancer: a cost-effectiveness analysis - Wai-kit Ming; Xiaoting Huang; Xiuhua Weng; Shen Lin; Yiwei Liu; Shaohong Luo; Hang Wang; Pinfang Huang (BMJ Open)
Objective The S0226 trial demonstrated that the combination of half-dose fulvestrant (FUL) and anastrozole (ANA) (F&A) caused a significant improvement in overall survival (OS) versus ANA monotherapy for first-line treatment of postmenopausal women with hormone receptor-positive metastatic breast cancer (PMW-MBC (HR+)). The objective of this study was to evaluate the cost-effectiveness of F&A in the first-line treatment for PMW-MBC (HR+) in China.Design We constructed a Markov model over a life-time horizon. The clinical outcomes and utility data were obtained from published literature. Cost data were obtained from official Chinese websites. Sensitivity analyses were performed to test result uncertainty.Setting Chinese healthcare system perspective.Population A hypothetical cohort of adult patients presenting with PMW-MBC (HR+).Interventions F&A compared with full-dose FUL and ANAmonotherapy.Main outcome measures The main outcome of this study was the incremental cost-effectiveness ratio (ICER) and quality-adjusted life-years (QALY).Results ANA was estimated to have the lowest cost and minimum life-years. The ICER of F&A versus ANA was US$15 665.891/QALY with incremental cost and QALY of US$12 401.120 and 0.792, respectively, which was less than the willingness-to-pay of US$29 383/QALY. Compared with F&A, FUL yielded a higher cost and a shorter lifetime; hence, it was identified as a dominated strategy. The univariate sensitivity analysis indicated the price of FUL was the most influential factor in our study. The probability that F&A was cost-effective at a threshold of US$29 383/QALY in China was 86.5%.Conclusion F&A is a cost-effective alternative to FUL and ANA monotherapy for the first-line treatment of PMW-MBC (HR+) in China. F&A is a promising first-line treatment for PMW-MBC (HR+), and more research is needed to evaluate the economy of using F&A in other countries.